Numerical simulation of a hot-air cleaning fan for the combine harvester - Tao Zhang; Guoliang You; Yaoming Li (PLoS ONE, 2026)
This study aimed to improve the separation efficiency of damp crops by developing a hot-air cleaning fan. First, the aerodynamic performance of two fans with different inlet structures was compared. The results showed a direct correlation between the static pressure and the outlet air velocity. The modified-inlet fan has an outlet average air velocity very close to the original fan of the combine harvester. Hence, the modified- inlet fan model was chosen for further analysis. Subsequent evaluations were conducted to assess the effects of fan speed, inlet air temperature, and volute temperature on fan performance. Fan speed exhibited a negative correlation with outlet air temperature but a positive correlation with outlet air velocity, at both the upper and lower outlets. Furthermore, both the inlet air temperature and the volute temperature were directly related to the air temperature at these outlets. A Response Surface Methodology (RSM) with three factors at three levels was utilized to optimize fan parameters, identifying fan speed and inlet air temperature as the predominant factors affecting outlet air velocity and temperature, respectively.The optimal set of parameters was determined to be a fan speed of 1445 rpm, an inlet temperature of 85 °C, and a volute temperature of 60 °C. Under these conditions, bench test results indicated the average air velocity and temperature are basically consistent with the theoretical optimal value.